EFFECT OF THE ROLE’S STAFF TO RESPOND’S MOTHER IN MONITORING MOTORIST GROWTH ONTO TODDLER (1-3 YEARS OLD) ( STUDY IN POSYANDU MELATI KENEP VILLAGE BALEN SUB-DISTRICT BOJONEGORO DISTRICT) - Nurustani Qurrata Ayunin; Endang Yuswa; Marxis Udaya (Jurnal Keperawatan, 2012)
Monitoring motorist growth of toddler is a very important thing to do beside growth of their body inPosyandu. Staff as medical government in Posyandu have important role to give counseling and informationabout the result of monitoring toddler growth. But the fact, when Posyandu’s Staff only give anthropometrycheckup, so that mother doesn’t understand the condition and doesn’t have any control to their toddleroptimally. Purpose of this research is to know the role of staff to respond’s mother in monitoring motoristgrowth of toddler in Posyandu Melati Kenep village Balen Sub-District Bojonegoro DistrictThis research design used cross sectional design. Population of this research is all of mother that havetoddler at 1-3 years old. With total samples as many as 57 persons by using sampling technique Proportionalsimple random sampling. Collecting data is held by using Questionnaire. Data is processed by using editing,coding, scoring, tabulating, and analyzed by using hi- Square testResult of this reserach shows that almost staff as many as 54% have passed good standard criteria, andsmall number of them as many as 46% didn’t passed good standard criteria. Respond’s mother mostly 60 %have positive respond, and small number of them 40% have negative respond in monitoring growth oftoddler. Result of chi square analyzing got that score p = 0,01 < 0,05.Conclusion of this research, there is effect of the role’s staff to respond’s mother in monitoring motoristgrowth onto toddler (1-3 years old)